2018
DOI: 10.2147/dddt.s179876
|View full text |Cite
|
Sign up to set email alerts
|

Asiatic acid ameliorates CC l<sub>4</sub>-induced liver fibrosis in rats: involvement of Nrf2/ARE, NF-&kappa;B/I&kappa;B&alpha;, and JAK1/STAT3 signaling pathways

Abstract: PurposeCurrently, there are no effective therapies for liver fibrosis; hence, the development of anti-liver fibrosis agents is urgently needed. Here, we attempted to investigate the therapeutic effect and mechanism of asiatic acid (AA) on liver fibrosis, mainly focusing on the impact of AA on nuclear erythroid 2-related factor 2/antioxidant response element (Nrf2/ARE), nuclear factor-kappa B (NF-κB)/IκBα, and JAK1/signal transducer and activator of transcription 3 (STAT3) signaling pathways.MethodsRats were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…This study confirmed the advantages of AR in the treatment of liver fibrosis with multiple targets and multiple pathways. In addition, it has been reported that Asiatic acid can ameliorate CCl 4 -induced liver fibrosis in rats by regulating PI3K/AKT/mTOR, Bcl-2/Bax, Nrf2/ARE, NF-κB/IκBα and JAK1/STAT3 signaling pathways [47, 48]. Salvia miltiorrhiza could inhibit liver fibrosis by regulating TGF-β/Smad, Nrf2/HO-1 and NF-κB/IκBα signaling pathways [49, 50].…”
Section: Discussionmentioning
confidence: 99%
“…This study confirmed the advantages of AR in the treatment of liver fibrosis with multiple targets and multiple pathways. In addition, it has been reported that Asiatic acid can ameliorate CCl 4 -induced liver fibrosis in rats by regulating PI3K/AKT/mTOR, Bcl-2/Bax, Nrf2/ARE, NF-κB/IκBα and JAK1/STAT3 signaling pathways [47, 48]. Salvia miltiorrhiza could inhibit liver fibrosis by regulating TGF-β/Smad, Nrf2/HO-1 and NF-κB/IκBα signaling pathways [49, 50].…”
Section: Discussionmentioning
confidence: 99%
“…24,40 It has been demonstrated that CCl 4intoxication results in the activation of liver macrophages 44 with the subsequent production of proinflammatory mediators including TNF-α which in turn exaggerate the CCl 4 -induced hepatic injury. 45,46 Furthermore, CCl 4 -induced free radicals lead to the activation of NF-κB and the release of inflammatory mediators into injured livers. 47 In parallel with these studies, our results revealed positive immunostaining of NF-κB and significant elevation of TNF-α in the hepatic tissue of the CCl 4 group compared to those of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The medicinal plant Centella asiatica (L) Urban also contains many NRF2-activating compounds. The plant contains high levels of four triterpene compounds, Asiatic acid, madecassic acid, asiaticoside, and madecassoside (MS) that have all been shown to activate NRF2 but do not possess strong electrophilic properties (Yang et al., 2016; Jiang et al., 2017; Fan et al., 2018; Liu et al., 2019c; Meng et al., 2019). Centella asiatica also contains many caffeoylquinic acids that we and others have shown can activate NRF2 as well (Boettler et al., 2011; Gray et al., 2014; Liang et al., 2019).…”
Section: Nrf Activating Compoundsmentioning
confidence: 99%